Digital Transformation of the Silk Industry of Assam - Hazarika, Indrani (Archives of Business Research, 2022)
The case study on the silk industry of Assam gives an overview of the industry, background, production process and highlights the key issues, which the industry is currently facing. In order to ensure strategic success, the traditional silk industry will have to effectively cope up with the digitalization challenge in the market for customer discovery. The raw material is locally available but limited in supply and there is no alternative source to cater the needs of the weavers. Therefore, the weavers are bound to pay high prices of raw materials. Though the cost of raw material is increasing, the weavers cannot increase the price of the products due to availability of cheap synthetic silk in the market and, they are compelled to compromise with the profit margin of the product. The entire silk industry of Assam is passing through a stagnation period not only because of the financial crisis but also due to rising prices and dearth of raw materials. This has resulted in aggravating the losses of the silk industry, as the weavers have to sell the products at the older price while procuring the raw material at the newly fixed price. The existing silk industry of Assam should go for complete digitalization through interconnected ecosystem, disrupt, and reshape the existing industry by identifying the technology associated with the business process and aligning with the business strategy. A digital culture needs to be fostered in the entire industry